Maintaining an Effective Circle: Volunteer Experiences of Operational Aspects of Circles of Support and Accountability - Lowe, Giulia (International journal of offender therapy and comparative criminology, 2019)
In Circles of Support and Accountability (CoSA), trained volunteers support an individual convicted for sexual offenses to reintegrate safely into the community. Developed in Canada, CoSA has been established in many jurisdictions with a growing number of volunteers; however, little is known about whether the training and support provided meets volunteer needs. Using a mixed-methods approach, the aim of the present research was to explore New Zealand CoSA volunteer experiences of the training and support they received and their perceptions about what contributed to the effective operation of a circle. In total, 18 volunteers took part in an interview and 23 volunteers completed a questionnaire. The findings found a mixed response to the training and support received, whereby some volunteers thought the training and support was adequate, whereas other felt the training support they received was inadequate. Findings also illustrate that adequate training, having access to a circle coordinator, selecting the right volunteers and core member, clear communication, and setting up boundaries were important factors in maintaining an effective circle. Findings are discussed in terms of implications for the training and support offered to current and future volunteers, as well as for maintaining the effectiveness of future circles.